Penerapan Nilai Pancasila dalam Umat Beragama di Masyarakat Sosial - A. Ramli Rasyid; A. Najwa Meisuri Sulolipu; Nabila; Muhammad Rifaat Taufiq Taufan (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to explore the application of Pancasila values in the lives of religious people in Indonesian social society. The literature study approach is used to investigate the social and cultural context of Indonesia, challenges, efforts, and conflicts related to the application of Pancasila values in the context of religious people. The results show that Indonesia, as a country rich in cultural and religious diversity, faces challenges in ensuring that the values of Pancasila can accommodate such diversity without sacrificing the unity and unity of the nation. Despite concrete efforts from various parties, including the government and civil society, to build tolerance and harmony between religious communities, conflict, discrimination, and intolerance remain relevant issues. There is a gap between the idealism of Pancasila and everyday practice, which is often triggered by differences in beliefs, political tensions, and socioeconomic issues. The implications of this study point to the need for concrete steps to address these challenges, including strengthening interfaith dialogue, promoting multicultural education, and implementing the values of Pancasila in daily life. Only with mutual cooperation and commitment can Indonesia maintain diversity and strengthen unity within the framework of Pancasila as the foundation of the country.